Nickel Diplomacy: The Geopolitics of Indonesia’s Downstream Policy and the Global Electric Vehicle Supply Chain - Kusuma, Darmawan Putra; Dewi, Komang Purnama; Atmika, Gede Surya (Universitas Negeri Semarang, 2025)
As the world pivots toward renewable energy, Indonesia has positioned itself as a pivotal player in the global Electric Vehicle (EV) supply chain by leveraging its status as the world’s largest nickel producer. This paper analyzes Indonesia’s